VALIDATING THE 3-STEP RETURN TO PLAY DECISION MAKING MODEL. Issue 7 (11th March 2014) - Shrier, I; Matheson, G; Boudier-Reveret, M; Steele, R
Abstract : Background: A recent return to play decision-making (RTP-DM) model for sport medicine has organized the underlying concepts into 3 steps but has not yet been validated. Objective: To examine the validity of the 3-step RTP-DM model recently proposed. Design: Repeated measures cross-over survey design. Setting: World-wide. Participants: American College of Sports Medicine clinicians involved in RTP-DM. Risk factor assessment: We provided clinical vignettes of injuries and illnesses in athletes to participants through an online survey. Each vignette included examples of 3 factor types: increasing injury severity, changing risk associated with sport (e.g. different positions), and changing non-injury risk factors (e.g. financial considerations). Main Outcome Measurements: For each vignette, participants indicated the level of activity restriction they would recommend (6 options from No Restrictions to No Activity) in accordance with the risk they placed on continued participation. We analyzed the data using multiple regression, adjusting for the correlated participant outcomes, to measure how changes in factors affected individual participants. Results: The estimated participation rate for those involved in RTP decisions was 24.7%. As expected, we found that clinicians increase restrictions as injury severity increases. We also found that changing factors related to sport risk, and changing factors that are unrelated to sport risk will affect RTP decisions, although the effect is context-dependent and does not occur equally across all injury severities and clinical cases. The effect was also observed in each subgroup examined that included sex, age, specialty, region of training, academic status, and years of experience making RTP decisions. Conclusions: Our findings that clinicians from a wide variety of backgrounds will change RTP recommendations based on clinical vignettes with changing injury severity, sport risk modifiers and decision modifiers provides evidentiary support for the 3-step model for RTP decision making recently proposed.